2018
DOI: 10.1186/s12879-017-2811-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of invasive group B streptococcal disease in infants from urban area of South China, 2011–2014

Abstract: BackgroundGroup B Streptococcus (GBS) is a leading cause of morbidity and mortality in infants in both developed and developing countries. To our knowledge, only a few studies have been reported the clinical features, treatment and outcomes of the GBS disease in China. The severity of neonatal GBS disease in China remains unclear. Population-based surveillance in China is therefore required.MethodsWe retrospectively collected data of <3 months old infants with culture-positive GBS in sterile samples from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 26 publications
6
34
3
1
Order By: Relevance
“…In our study, the most frequent early-onset pathogens causing the infant infections were GBS and E. coli, which is consistent with the results from previous studies (8,10,11). Other pathogens were notably less frequent.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the most frequent early-onset pathogens causing the infant infections were GBS and E. coli, which is consistent with the results from previous studies (8,10,11). Other pathogens were notably less frequent.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that serotype III was the most common type (61.2%). Other studies also have reported the comparable proportion of serotype III in China ( 7 , 22 24 ). In general, GBS serotype distributions were similar across regions of China, and were similar to findings for other countries, with serotype III dominating (61.5%) and serotypes Ia, Ib, II, III, and V causing 97% of invasive GBS disease ( 3 ).…”
Section: Discussionmentioning
confidence: 62%
“…GBS is associated with severe neonatal infection in some hospitals in China ( 7 , 12 – 16 ), but a paucity of generalizable data is available across the country. We conducted a large, multicenter study to evaluate the clinical and molecular epidemiology of invasive group B streptococcal disease among infants < 3 months of age in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Several studies have reported 0.55e1.79 cases of neonatal GBS per 1000 live births, with a CFR of 6.45e7.1%. 8,9 Therefore, physicians should pay great attention to GBS infection, relevant research should be actively performed, and appropriate guidelines for the diagnosis and treatment of GBS should be formulated to prevent or reduce the incidence of neonatal GBS infection and improve maternal and infant outcomes.…”
Section: Epidemiologymentioning
confidence: 99%